The Effect of Technical Entrepreneurship Training on the Entrepreneurial Ability of Training Participants at the Technical Implementation Unit for Social Welfare Enhancement in Malang - Putri, Vita Kusuma; Supriyono, Supriyono; Sucipto, Sucipto (Universitas Negeri Malang, 2024)
The aim of this research was to determine the effect of technical entrepreneurship training on the entrepreneurial abilities of training participants at the UPT PTKS Malang institution. The approach used in this research is quantitative. This research used a population of 40 participants and a sample of 30 training participants. Meanwhile, the data analysis technique uses simple linear regression analysis. This research found that t count > t table, namely 0,020 which is significantly smaller than 0.005, namely (0.000 < 0.005) entrepreneurial technical training has a significant influence on entrepreneurial ability of 38,4% and the remaining is influenced by other variables. Suggestions based on the results of the analysis that have been carried out, it can be seen that technical entrepreneurship training has affected the entrepreneurial abilities of training participants at the UPT PTKS Malang institution, but the influence of the training variable has not reached 50%, therefore it is necessary to increase improvements in terms of training intensity and quality of training so that the program Entrepreneurship training is able to influence the entrepreneurial abilities of training participants at the UPT PTKS Malang institution to a greater extent than before.